Utility of Nontraditional Risk Markers in Individuals Ineligible for Statin Therapy According to the 2013 American College of Cardiology/American Heart Association Cholesterol Guidelines. Issue 10 (8th September 2015) - Yeboah, Joseph; Polonsky, Tamar S.; Young, Rebekah; McClelland, Robyn L.; Delaney, Joseph C.; Dawood, Farah; Blaha, Michael J.; Miedema, Michael D.; Sibley, Christopher T.; Carr, J. Jeffrey; Burke, Gregory L.; Goff, David C.; et al.
<x xml:space="preserve">Abstract</x> Background— In the general population, the majority of cardiovascular events occur in people at the low to moderate end of population risk distribution. The 2013 American College of Cardiology/American Heart Association guideline on the treatment of blood cholesterol recommends consideration of statin therapy for adults with an estimated 10-year atherosclerotic cardiovascular disease (ASCVD) risk ≥7.5% based on traditional risk factors. Whether use of nontraditional risk markers can improve risk assessment in those below this threshold for statin therapy is unclear. Methods and Results— Using data from the Multi-Ethnic Study of Atherosclerosis (MESA), a population sample free of clinical CVD at baseline, we calibrated the Pooled Cohort Equations (cPCE). ASCVD was defined as myocardial infarction, coronary heart disease death, or fatal or nonfatal stroke. Adults with an initial cPCE <7.5% and elevated levels of additional risk markers (abnormal test) whose new calculated risk was ≥7.5% were considered statin eligible: low-density lipoprotein cholesterol ≥160 mg/dL; family history of ASCVD; high-sensitivity C-reactive protein ≥2 mg/dL; coronary artery calcium score ≥300 Agatston units or ≥75th percentile for age, sex, and ethnicity; and ankle-brachial index <0.9. We compared the absolute and relative ASCVD risks among those with versus without elevated posttest estimated risk. We calculated the number needed to screen to identify 1 person with abnormal test for each risk marker, defined as the number of participants with baseline cPCE risk <7.5% divided by the number with an abnormal test reclassified as statin eligible. Of 5185 participants not taking statins with complete data (age, 45–84 years), 4185 had a cPCE risk <7.5%. During 10 years of follow-up, 57% of the ASCVD events (183 of 320) occurred among adults with a cPCE risk <7.5%. When people with diabetes mellitus were excluded, the coronary artery calcium criterion reclassified 6.8% upward, with an event rate of 13.3%, absolute risk of 10%, relative risk of 4.0 (95% confidence interval [CI], 2.8–5.7), and number needed to screen of 14.7. The corresponding numbers for family history of ASCVD were 4.6%, 15.1%, 12%, 4.3 (95% CI, 3.0–6.4), and 21.8; for high-sensitivity C-reactive protein criteria, 2.6%, 10%, 6%, 2.6 (95% CI, 1.4–4.8), and 39.2; for ankle-brachial index criteria, 0.6%, 9%, 5%, 2.3 (95% CI, 0.6–8.6), and 176.5; and for low-density lipoprotein cholesterol criteria, 0.5%, 5%, 1%, 1.2 (95% CI, 0.2–8.4), and 193.3, respectively. Of the 3882 with <7.5% cPCE risk, 431 (11.1%) were reclassified to ≥7.5% (statin eligible) by at least 1 of the additional risk marker criteria. Conclusions— In this generally low-risk population sample, a large proportion of ASCVD events occurred among adults with a 10-year cPCE risk <7.5%. We found that the coronary artery calcium score, high-sensitivity C-reactive protein, family history of ASCVD, and ankle-brachial index recommendations by the American College of Cardiology/American Heart Association cholesterol guidelines (Class IIB) identify small subgroups of asymptomatic population with a 10-year cPCE risk <7.5% but with observed ASCVD event rates >7.5% who may warrant statin therapy considerations.